Planungskultur in action. Eine komplexitätstheoretische und praxisorientierte Annäherung an Planungskultur. - Loepfe, Matthias; Eisinger, Angelus (Routledge, 2016)
Der Beitrag befasst sich mit einer Weiterentwicklung der theoretischen Fundierung des Planungskultur-Ansatzes als analytischer Ansatz. Die Autoren diskutieren die Verwendung des Planungskultur-Begriffes in der Praxis und erweitern das theoretische Verständnis um Ansätze der sozialen Komplexität. Die Autoren illustrieren einen andersgearteten analytischen Zugang zu Planungskultur, das Denken in Möglichkeitsräumen, welcher anhand der schweizerischen Raumplanungspraxis exemplarisch dargestellt wird.

Based on a brief review of practiceoriented meanings of "planning culture", we observe the following: Firstly, planning culture unites in practice what is strictly separated in theory. Thus, the normative and contentrelated moment of evaluation always goes hand in hand with an analytical-interpretative moment of the preforming of perspectives and possibilities. Secondly, planning culture in practice is a "fuzzy concept", which despite displaying considerable potential for associative power, also conceals the complexity of planning contents and processes. Thirdly, planning culture is expressed in two ways in planning processes: on the one hand, in plan worlds, and on the other hand, in the specific implementation of these plan worlds and the associated networks. In order to provide a theoretical foundation for these observations, we refer to the theories of social complexity and introduce the concepts that we believe are central. On this basis, we establish our analytical approach to planning culture: thinking in possibilities. Finally, we illustrate this approach using the results of an empirical study carried out in Switzerland on the practice of the planning instrument "test planning". Thinking in possibilities not only offers a promising analytical approach to planning cultures, but also helps to draw conclusions on the content of planning practice: planning culture should be negotiated more explicitly in practice. At the very least, the implicit normative assumptions should be reflected on, since they often restrict the range of possible and conceivable solutions all too early.
Planning culture in action. A practice-oriented approach to planning culture on the basis of complexity thinking.
Keywords: Stadtplanung; Raumplanung; Planungsprozess; Planungstheorie; Planungspraxis; Wirkung; Reflexion; Planungskultur; Begriff; Akteur; Planungsinhalt; Komplexität; Testplanung; Planungsinstrument